Establishing the Bases for Introducing the Unexplored Portuguese Common Bean Germplasm into the Breeding World - Leitão, Susana T.; Dinis, Marco; Veloso, Maria M.; Šatović, Zlatko; Vaz Patto, Maria C. (Frontiers in Plant Science, 2017)
Common bean is among the most important grain legumes for human consumption worldwide. Portugal has a potentially promising common bean germplasm, resulting from more than five centuries of natural adaptation and farmers’ selection. Nevertheless, limited characterization of this resource hampers its exploitation by breeding programs. To support a more efficient conservation of the national germplasm and promote its use in crop improvement, we performed, for the first time, a simultaneous molecular marker (21 microsatellites and a DNA marker for phaseolin-type) and seed and plant morphological characterization (14 traits) of 175 accessions from Portuguese mainland and islands traditional bean-growing regions. A total of 188 alleles were identified and an average genetic distance of 0.193 was estimated among accessions. To relate the Portuguese germplasm with the global common bean diversity, 17 wild relatives and representative accessions from the Andean and Mesoamerican gene pools were evaluated at the molecular level. No correlation was detected between the variability found and the geographic origin of accessions. Structure analysis divided the collection into three main clusters. Most of the Portuguese accessions grouped with the race representatives and wild relatives from the Andean region. One third of the national germplasm had admixed genetic origin and might represent putative hybrids among gene pools from the two original centers of domestication. The molecular marker-based classification was largely congruent with the three most frequent phaseolin haplotype patterns observed. Seed and plant morphological characterization of 150 Portuguese common bean accessions revealed a clear separation among genetic structure and phaseolin haplotype groups of accessions, with seed size and shape and the number of locules per pod the most discriminant traits. Additionally, we used molecular and morphological data to develop a series of smaller core collections that represents the Portuguese common bean germplasm with minimum repetitiveness. A core collection with 37 accessions contained 100% of the genetic variation found in the entire collection. This core collection is appropriate for a more detailed characterization and should be explored, as a priority, in national and international common bean breeding efforts. Furthermore, the identified intermediate accessions, may have novel genetic combinations useful in future bean breeding.